Budgeting Management for the Top Priority and National Priority Programs of Nawacita - Biswan, Ali Tafriji; Farida, Fitria Nur; Sandi, Hendrik Heri (Jurnal Manajemen dan Keuangan, 2023)
Among many of the government-sector programs are the Top Priority and National Priority Programs. These programs translate the government's vision, which is known as Nawacita. It is undeniable that the Top Priority and National Priority Programs certainly require a budget. However, whether the Top Priority and National Priority programs received preferential treatment in budgeting still became an issue. For this reason, this study was intended to analyze whether there was any special treatment given to the budgeting process compared to other programs in general. This qualitative research utilized a case study model based on observations, interviews, and literature studies on Performance-Based Budgeting (PBB) management in the public sector. It was revealed that there was no special treatment for budgeting the Top Priority and National Priority Programs. This study also found several problems related to the budgeting coordination, so that activity plans were not fully following the budget. Finally, this study suggested that a greater need for budgeting skills and the importance of detailing budget information were also crucial.